Efektivitas Model Pembelajaran ARCSI dengan Pendekatan Saintifik Terhadap Hasil Belajar Matematika Siswa SMP - Usmadi Usmadi; Ergusni Ergusni (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
This research is based on the emergence of the 2013 curriculum which expects a learnng process that can make students actively construct their knowledge. The effectiveness of ARCSI learning models with a scientific approach can be seen from student learning outcomes, through 1) Student Worksheets (LKPD), 2) Test of learning outcomes. The results of the study show that the learning model developed is effective when viewed from students' mathematics learning outcomes. The level of effectiveness of the ARCSI learning model with a scientific approach obtained the results of LKIPD grades VII1 SMP N 7 and class VII1 SMP N 1 Ampek Angkek is categorized as effective with a mean of 75.017. The level of effectiveness of ARCSI learning models with a scientific approach obtained from the value of test questions on cognitive learning outcomes is categorized as effective with a mean of 61.38. Based on the hypothesis test for mathematics learning outcomes data can be drawn conclusions, namely: 1) Mathematics learning outcomes of class VII1 students (experimental class) is better than the mathematics learning outcomes of class VII4 students (control class) SMP N 7 Bukittinggi city; 2) Mathematics learning outcomes of class VII1 students (experimental class) are better than mathematics learning outcomes of class VII2 students (control class) Ampek Angkek N 1 junior high school in Agam district